Micrometric patterning of luminescence and second order optical properties of a terbium containing borogermanate magneto-optical glass by thermal poling - Orives, Juliane Resges [UNESP]; Marcondes, Lia Mara [UNESP]; Karam, Lara; Adamietz, Frédéric; Cardinal, Thierry; Nalin, Marcelo [UNESP]; Dussauze, Marc (My University, 2024)
A thermo-electrical imprinting process on a borogermanate glass containing Tb3+ have permitted a micrometric structuring of the oxidation state of Tb ions. Correlative luminescence, Raman and SHG microscopies demonstrate modification of the glass structure accompanying large luminescence changes and the appearance of an electro optical response.